Religious socialization of non-religious university students. Issue 2 (3rd April 2019) - Dahl, Karoliina; Novis-Deutsch, Nurit; Klingenberg, Maria; Kontala, Janne; Sztajer, Sławomir; Mussel, Avivit
ABSTRACT: Studies of non-religion and youth raise questions regarding the conceptual usefulness of religious socialization. If religious socialization is studied only as the extent to which intergenerational transmission of religiosity occurs, the religious socialization of those who identify as non-religious falls out of the scope of research. This article explores the religious socialization of a group of university students from Sweden, Finland, Poland, and Israel who identify as non-religious. Interviews with these young adults allow us to explore the (religious) socialization of non-religious individuals in different contexts. The findings point to how the influence of socialization agents turned some of the students onto a path towards non-religion. Others, in turn, are characterized by family backgrounds where religion has not played any significant part. Our findings indicate that religious socialization, broadly construed, can be a useful perspective for understanding varying paths towards non-religiosity.